PENGARUH LATIHAN JALAN CEPAT UNTUK MENINGKATKAN DAYA TAHAN KARDIORESPIRASI DAN MENINGKATKAN DAYA TAHAN KARDIORESPIRASI MAHASISWA JURUSAN FISIOTERAPI - Asriani, Dwi Suci; Handoko, Bobi; Ahmad, Fabian (LPPM Universitas Awal Bros, 2025)
Cardiorespiratory endurance is a vital component of physical fitness, especially for physiotherapy students who will be engaged in physically demanding activities and healthcare services. Brisk walking is a simple, low-cost, and effective aerobic exercise to improve cardiorespiratory endurance. This community service activity aimed to educate and engage physiotherapy students in brisk walking exercises to enhance their physical fitness. The program included fitness education sessions, initial VO₂ max assessments, multiple brisk walking training sessions, and final evaluations. The results indicated an improvement in students' cardiorespiratory capacity following the exercise program. This initiative is expected to inspire students to adopt an active and healthy lifestyle in the long term.